2020
DOI: 10.1039/c9dt04562g
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient uranium grabber derived from acrylic fiber for extracting uranium from seawater

Abstract: An amidoxime and carboxylate containing chelating adsorbent derived from acrylic fiber shows a fast adsorption rate and high uranium and low vanadium adsorption capacities in real seawater tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
2
28
1
Order By: Relevance
“…Recently, a group at the University of Tennessee in collaboration with Oak Ridge National Laboratory achieved the highest‐ever recorded uranium adsorption of 6.56 g‐uranium/kg‐adsorbent following 56 days of seawater submersion employing amidoximated polymer adsorbents prepared by the atom‐transfer radical polymerization (ATRP) technique 36 . Moreover, Pan et al recently achieved the high uranium adsorption of 6.02 g‐uranium/kg‐adsorbent and estimated the saturation capacity of 7.73 g‐uranium/kg‐adsorbent by employing amidoxime‐ and carboxylate‐containing fiber adsorbent for 56 days of soaking in filtered natural seawater 35 . Even though the maximum adsorption achieved in the present study is only 1.39 mg/g adsorbent for 42 days of submersion, the experiments were performed at a relatively small SWRO plant with the relatively low brine concentrate discharge rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a group at the University of Tennessee in collaboration with Oak Ridge National Laboratory achieved the highest‐ever recorded uranium adsorption of 6.56 g‐uranium/kg‐adsorbent following 56 days of seawater submersion employing amidoximated polymer adsorbents prepared by the atom‐transfer radical polymerization (ATRP) technique 36 . Moreover, Pan et al recently achieved the high uranium adsorption of 6.02 g‐uranium/kg‐adsorbent and estimated the saturation capacity of 7.73 g‐uranium/kg‐adsorbent by employing amidoxime‐ and carboxylate‐containing fiber adsorbent for 56 days of soaking in filtered natural seawater 35 . Even though the maximum adsorption achieved in the present study is only 1.39 mg/g adsorbent for 42 days of submersion, the experiments were performed at a relatively small SWRO plant with the relatively low brine concentrate discharge rate.…”
Section: Resultsmentioning
confidence: 99%
“…36 Moreover, Pan et al recently achieved the high uranium adsorption of 6.02 guranium/kg-adsorbent and estimated the saturation capacity of 7.73 g-uranium/kg-adsorbent by employing amidoxime-and carboxylate-containing fiber adsorbent for 56 days of soaking in filtered natural seawater. 35 Even though the maximum adsorption achieved in the present study is only 1.39 mg/g adsorbent for 42 days of submersion, the experiments were performed at a relatively small SWRO plant with the relatively low brine concentrate discharge rate. A larger SWRO plant with a much higher brine concentrate flow rate should result in higher adsorption.…”
Section: Performance Of Amidoxime Adsorbent At Swro Plant With Diffmentioning
confidence: 87%
See 1 more Smart Citation
“…The conversion of PAN to PAO is fairly dependent on amidoximation conditions (such as amidoximation time, temperature and NH 2 OH concentration). 9,[17][18][19][20][21][22][23] High temperature, high NH 2 OH concentration and a long reaction time benet the diffusion of NH 2 OH from solution into the PAN matrix and enhance PAN conversion and H 2 L I formation. 13,14,21 However, because of the instability of PAO, unproper amidoximation conditions result in the degradation and decomposition of PAO.…”
Section: Introductionmentioning
confidence: 99%
“…10,13,[24][25][26] Rao et al 27,28 reported that open-chain AO and cyclic imide dioximes are the major products of PAO at low and high temperatures, respectively. Moreover, the U/V selectivity and the conversion of the ester group (-C] O) to carboxylate (-COO À ) on adsorbent surface depend on the amidoximation condition, 18 which is important for applying PAObased adsorbents. Therefore, it is necessary to characterize the transformation of PAN to PAO during the amidoximation process, which can provide pivotal information for optimizing amidoximation conditions, and then improve its adsorption capability for trace U(VI) in seawater.…”
Section: Introductionmentioning
confidence: 99%